Effect of the laser texturing width on hot-pressing joining of AZ31B and CFRTP. (November 2021) - Liu, Yifan; Su, Jianhui; Ma, Guolong; Han, Xiaohui; Tan, Caiwang; Wu, Laijun; Chen, Bo; Song, Xiaoguo
Highlights: Investigate effect of various widths of laser textured groove on the joint. Identify a new chemical bonding MgCO3 at the interface after joining. A number of AZ31B matrix was observed on the CFRTP at the interface. The joints broke at the CFRTP base material after laser texturing. Abstract: Laser texturing was performed on the surface of AZ31B magnesium alloy to increase the bonding strength. Textured AZ31B and carbon fiber reinforced thermoplastics (CFRTP) were then joined by the hot-pressing joining process. The effect of various groove widths of laser textured grid on the AZ31B/CFRTP joint was investigated. The research results showed that the wettability of the molten CFRTP on laser textured AZ31B was increased by about nine times, and the contact angle was reduced from 104.0° to 48.8° with a groove width of 0.3 mm. The macroscopic morphology and interface of joints had no defects, when the groove widths were 0.2 mm and 0.3 mm. The tensile-shear test was carried out, and the maximum tensile-shear force of the joint was 2698.8 N in the case of 0.3-mm groove width, which was 2.1 times as much as that of the untreated joint. The maximum tensile-shear force was 65.43% of the CFRTP itself. A diffusion layer of 9 μm– 24 μm thick formed at the AZ31B/CFRTP joint. MgCO3 was identified at the joining interface. The mechanical interlocking and chemical bonding formed at the interface effectively improved the strength of the joint.